Implant dentistry at-a-glance - Malet, Jacques; Mora, Francis; Bouchard, P. (Philippe) (Chichester, West Sussex, UK : Wiley-Blackwell, 2012)
'This is the latest title in the highly popular at a Glance series. It provides a concise and accessible introduction and revision aid, comprehensively covering all the constituent sub-topics that comprise implant dentistry. Following the familiar, easy-to-use at a Glance format, each topic is presented as a double-page spread with facts accompanied by clear diagrams and clinical photographs encapsulating essential information.Implant Dentistry at a Glance is an ideal companion for all students of dentistry, junior clinicians and members of the dental team with an interest in implant dentistry'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Dental Implantation; Dental Implants; Oral Surgical Procedures -- methods